Physical Performance Limitations After Severe Lower Extremity Trauma in Military Service Members. Issue 4 (April 2018) - Wilken, Jason M.; Roy, Catherine W.; Shaffer, Scott W.; Patzkowski, Jeanne C.; Blanck, Ryan V.; Owens, Johnny G.; Hsu, Joseph R.
Abstract : Objectives: To characterize the type and magnitude of lower extremity physical performance deficits in military service members who have undergone rehabilitation after limb salvage or transtibial amputation. Design: Cross-sectional prospective. Setting: Level I trauma military medical and rehabilitation center. Patients/Participants: Service members with lower extremity trauma resulting in limb salvage (n = 20) or unilateral transtibial amputation (n = 14) compared with uninjured actively training service members (n = 123). Intervention: Control participants and individuals with amputation were tested during a single session. Participants with limb salvage were tested with and without the use of a custom carbon fiber orthosis. Main Outcome Measurements: Physical performance as measured using four-square step, sit-to-stand 5 times, and timed stair ascent tests. Secondary outcomes included the associations between these lower extremity activity measures to determine the interrelationship of activity limitations. Results: The ability of service members to rapidly ascend stairs, a demanding lower limb mobility task, is limited after amputation and limb salvage. However, performance on an agility test similar to the four-square step test approximated normative levels. Differences between individuals with amputation or limb salvage were less than 1 second for all tests and were not statistically significant. Correlations were observed among the physical performance measures in the tested patient populations, particularly between the sit-to-stand and timed stair ascent tests. Conclusions: Severe limb trauma significantly affects performance, particularly during tasks requiring lower extremity strength and power. Individuals with amputation or limb salvage who were provided a custom carbon fiber orthosis and intensive rehabilitation had similar performance. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.